Knowledge Level of Farmers about Cultivation of Quinoa (Chenopodium quinoa Willd.) in Cold Arid Region of Ladakh (Indian Journal of Extension Education, 2021)
The study investigated the knowledge level of farmers about the recommended cultivation practices of quinoa (a high value crop and potential option for crop diversification) in cold arid region of Ladakh.A total sample of 80 farmers was randomly selected from two villages (Thiksay and Stakana), where it was largely adopted by the farmers after its introduction in the region during 2016 onwards. The data were collected with the help of pre-structured interview schedule for the major cultivation practices during 2020. The knowledge level of farmers about timing of irrigation was observed highest followed by spacing, germination of seeds, thinning, recommended fertilizers, date of sowing, seed rate, first weeding, harvesting, market rate, and varieties of quinoa. Further, it was observed that majority of the farmers had medium level of knowledge about quinoa cultivation. It means that there is large scope for imparting training to the farmers about adoption of improved cultivation practices so as to increase the production of this highly remunerative crop and help in increasing the livelihood of farmers in the region.